The Codex Geometry and its Semiotics - Sánchez Prieto, Ana Belén (Eikón / Imago, 2012)
The page layout of a book is a design made of various rectangles that normally keep certain proportions. In present times the size and proportions of these rectangles are determined by practical and esthetical causes, but in the Middle Ages Geometry was known to be considered as a mean of metaphysical meditation. This article deals with the possible metaphysical interpretation of measures and proportional rectangles as they appear in mediaeval manuscripts.